Plannar Microwave Imaging System - Asefi, Mohammad (2011)
A Master of Science Thesis in Electrical Engineering submitted by Mohammad Asefi entitled "Plannar Microwave Imaging System," submitted in May 2011. Available are both soft and hard copies of the thesis.